Danger on the plate: human health risks derived from the consumption of angular angelshark (Squatina guggenheim) meat in southeastern Brazil - Lopes, Amanda Pontes; Coutinho, Rebeca Dias de Souza; Saint’Pierre, Tatiana Dillenburg; Hauser-Davis, Rachel Ann (Frontiers in Toxicology, 2025)
IntroductionShark and ray species are particularly vulnerable to pollutant bioaccumulation, including metals and metalloids, due to their k-strategist characteristics and mid–high trophic level. The angular angelshark (Squatina guggenheim) is a benthic and highly endangered species distributed from southeastern Brazil to southern Argentina. Despite being threatened with extinction and banned from marketing and consumption in Brazil, it is still widely consumed in several states. However, studies addressing metal and metalloid contamination in the meat of this species have not yet been conducted in Brazil.ObjectivesThis study aimed to determine metal and metalloid contamination levels in S. guggenheim and to assess human health risks associated with its consumption by infants, children, teenagers, and adults, considering consumption frequencies ranging from one to five times per week.Resultsetal and metalloid concentrations in muscle tissue were generally lower than those reported for other benthic Squatinidae species, except for Pb and Rb. Several elements were reported for the first time in this species, providing baseline data. Although a favorable Se:Hg balance suggested a potential protective effect, multiple toxic and potentially toxic elements were detected, posing significant human health risks, particularly for infants and children. Arsenic concentrations exceeded Brazilian safety limits, while Ti and Rb were present at relatively high levels, despite the absence of established regulatory thresholds. Estimated intake values and non-carcinogenic risk indices (THQ and HI) surpassed safety limits for As (notably the inorganic As 10% fraction), Cu, MeHg, and Se in different scenarios, with As exceeding the acceptable threshold by up to 415 times, even under low-frequency consumption. Carcinogenic risk (CR) estimates indicated concerning levels for As and Pb across age groups.ConclusionsThe results highlight significant human health risks associated with the consumption of S. guggenheim, particularly for vulnerable populations such as infants and children. These findings highlight the urgent need for continuous monitoring of benthic elasmobranchs and reinforce caution regarding their consumption.